The Currency of Reciprocity: Gift Exchange in the Workplace - Kube, Sebastian; Maréchal, Michel André; Puppe, Clemens (American Economic Review, 2012)
What determines reciprocity in employment relations? We conducted a controlled field experiment to measure the extent to which monetary and nonmonetary gifts affect workers' performance. We find that nonmonetary gifts have a much stronger impact than monetary gifts of equivalent value. We also observe that when workers are offered the choice, they prefer receiving money, but reciprocate as if they received a nonmonetary gift. This result is consistent with the common saying, “it's the thought that counts.” We underline this point by showing that monetary gifts can effectively trigger reciprocity if the employer invests more time and effort into the gift's presentation.